1968
DOI: 10.1177/002224376800500111
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of Product Bias

Abstract: This article establishes the concept and measure of the elasticity of product bias. It demonstrates that, for most consumers, the effect of product bias on the selection decision between similar, alternative domestic and foreign goods can be offset by manipulation of the price differential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…In general, older and/or higher-educated people tend to favor foreign products (Schooler, 1971); and consumer quality perceptions are positively related to a country's level of economic development (Pecotich, Pressley, & Roth, 1996). The effect of consumer bias against products from less developed countries can be offset only by price reductions (Bruning, 1997;Schooler & Wildt, 1968) and the bias is difficult to change (Kotler & Gertner, 2002) unless it is alleviated by some unusual events such as the 2008 Summer Olympics in China or the World Cup 2010 in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, older and/or higher-educated people tend to favor foreign products (Schooler, 1971); and consumer quality perceptions are positively related to a country's level of economic development (Pecotich, Pressley, & Roth, 1996). The effect of consumer bias against products from less developed countries can be offset only by price reductions (Bruning, 1997;Schooler & Wildt, 1968) and the bias is difficult to change (Kotler & Gertner, 2002) unless it is alleviated by some unusual events such as the 2008 Summer Olympics in China or the World Cup 2010 in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effects of country image (CoI) on consumers' purchasing behavior have been the subject of ongoing attention of academic marketing literature since one of the first studies in this area (Schooler, 1965;Schooler & Wildt, 1968). As this stream of research reaches maturity, the relevance of country image is facing challenges (e.g., Usunier, 2006, versus Josiassen & Harzing 2008Samiee, 2009, versus Roth & Diamantopoulos, 2009, 2010 due to structural changes in international markets-such as increasing economic globalization (Pharr, 2005;Usunier, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Dichter (1962) was among the first to demonstrate that country of origin can influence whether products are accepted or successful. Later, Schooler and Wildt (1968) carried out an empirical test using glassware identical in every respect, except for the country of origin, and concluded that they were evaluated differently.…”
Section: Country Of Originmentioning
confidence: 99%
“…Some studies have questioned the importance of the country of origin for many consumer decision making (Elliott and Cameron, 1994;Hugstad and Durr, 1986;Mitchell and Greatorex, 1990;Schooler and Wildt, 1968), recent research has described that the home country has a huge effect on the attitude toward the product and the possibility of purchasing this product, it is often to show the similar stronger effect or even more powerful than the brand name, price, or quality (Ahmed and d'Astous, 1996;Lantz andLoeb, 1996, Okechuku, 1994).…”
Section: Consumer Ethnocentrism and Growing Consumer Trendmentioning
confidence: 99%